Great Indian Economists vol.3 Their creative vision for socio-economic development - Dr. B.R. Ambedkar - Das, Debendra Kumar (ed) (New Delhi Deep & Deep Publications, 2004)
Dr. B.R. Ambedkar- life sketch and socio- economic philosophy